Dojrzewanie do własnego głosu, czyli „Rejwach” Mikołaja Grynberga (Politeja, 2020)
Maturing to One’s Own Voice, or ‘Rejwach’ by Mikołaj GrynbergThe early books by Mikołaj Grynberg containing conversations with survivors and their children allowed the writer to discover perspectives unknown to him before. With time these stories, combined with his own experiences, have become the basis for writing ‘Rejwach’. In the article, while introducing the author’s search for form, the author will show how the contemporary writing about the Holocaust has evolved. Grynberg, on the basis of testimonies he has heard, creates stories which many people affected by the Holocaust can identify with – people from the first, second and even third generation of survivors. Although fictitious, they have a universal value.